(untitled) (Journal of Ideas in Health, 2025)
Background: Minimally invasive spine surgery (MIS) is increasingly preferred over traditional open surgery due to its advantages. Anesthesia choice plays a key role in surgical outcomes. This study compares spinal anesthesia (SA) and general anesthesia (GA) in patients undergoing scheduled MIS for lumbar spine conditions. Methods: This prospective randomized study was conducted in Parul Sevashram Hospital, Parul University, Vadodara, Gujarat, between May 2024 and October 2024. The study included 34 ASA-1 and ASA-2 patients scheduled for one—or two-level MIS, divided into two groups: Group G (GA) and Group S (SA). Preoperative evaluation included demographics, lab tests, and imaging. Intraoperative monitoring covered heart rate, mean arterial pressure, and oxygen saturation. Postoperative assessments included blood loss, satisfaction scores, and complications. Results: Spinal anesthesia (SA) showed better hemodynamic stability, reduced blood loss (67.5±19.8 ml in Group S vs 73.2±14.9 ml in Group G), and higher satisfaction scores. Surgery duration was shorter in the SA group (89.9±8.2 min in Group S vs 94±7.2 min in Group G), with fewer complications. PACU stay was significantly lower in Group S (134±17.2 min) compared to Group G (175±20.4 min). Postoperative analgesic requirement (Inj Butorphanol) was also less in Group S (5 mg vs 14 mg IV). Conclusion: Spinal anesthesia is a safe and effective alternative to general anesthesia for MIS, offering better patient outcomes and satisfaction. This study supports the broader use of spinal anesthesia in suitable candidates to improve perioperative care.